2022
DOI: 10.1038/s41388-022-02199-9
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin E3 ligase ARIH1 regulates hnRNP E1 protein stability, EMT and breast cancer progression

Abstract: The epithelial to mesenchymal transition (EMT), a process that is aberrantly activated in cancer and facilitates metastasis to distant organs, requires coordinated transcriptional and post-transcriptional control of gene expression. The tumor-suppressive RNA binding protein, hnRNP-E1, regulates splicing and translation of EMT-associated transcripts and it is thought that it plays a major role in the control of epithelial cell plasticity during cancer progression. We have utilized yeast 2 hybrid screening to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…ARIH1 is a component of the CRL system and regulates cancer progression and xenophagy of cytosolic bacteria 46 , 49 51 . Since ARIH1 interacts with cGAS that mediates innate antiviral responses, we investigated the role of ARIH1 in HSV-1- or cytoplasmic DNA-triggered immune signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARIH1 is a component of the CRL system and regulates cancer progression and xenophagy of cytosolic bacteria 46 , 49 51 . Since ARIH1 interacts with cGAS that mediates innate antiviral responses, we investigated the role of ARIH1 in HSV-1- or cytoplasmic DNA-triggered immune signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed a suppressive role of ARIH1 in tumorigenesis 49 , 51 . A more recent report has shown that ARIH1 catalyzes ubiquitination and degradation of PD-L1 and thereby promotes anti-tumor immunity and that the expression of ARIH1 is severely suppressed in lung adenocarcinoma biopsies 51 .…”
Section: Discussionmentioning
confidence: 99%
“…For cancer cells, Vimentin consequently led to metastasis and immune escape through the expression of PD-L1 in LUAD by triggering the TGF-b/SMAD2 signaling (44). In addition, ARIH1 (or HHARI) known as a ubiquitin-protein ligase, contributed to EMT induction and breast cancer progression (45,46). However, Wu et al found that the overexpression of ARIH1 could suppress tumor growth and promote cytotoxic T cell activation by inducing PD-L1 degradation (47).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-suppressive RBP, hnRNP-E1, is known to modulate splicing and translation of the epithelial to mesenchymal transition (EMT)-associated transcripts and to play a major role in the control of epithelial cell plasticity during cancer progression. The ARIH1, an E3 ubiquitin ligase, can target and interfere with the activity of this RBP by degrading it and promoting breast cancer progression [ 109 ]. The RBP DDX41 is a tumor suppressor that opposes double-strand DNA breaks, genomic instability, and R-loop-dependent replication stress by preferentially binding RNA–DNA hybrids and unwinding RNA–DNA hybrids in R-loops, and also reduces the fragility of DNA in promoter regions [ 39 ].…”
Section: Rbps Assume Diverse Types Of Functions In Mammalian Cellsmentioning
confidence: 99%